AN ANALYSIS BEHAVIORAL OF MAIN CHARACTER IN HARRY POTTER AND THE GOBLET OF FIRE MOVIE DIRECTED BY MIKE NEWELL - muji Endah palupi (STIBA IEC JAKARTA, 2022)
The purpose of this study is to analyze behavioral of the main character in the film. The main character Harry in the film Harry Potter and the Goblet of Fire. The main behavior is seen from actions and emotions that are based on environment. Harry's character is a genius, all problem he goes make him developing charge of character and mental psychology. Problems do not only come from oneself but also from the environment and mental condition. Behavior that affects people around him, including himself. The impact of Harry's character behavior leads to psychology and sociology, especially in mental psychology, Harry's character becomes main character of each problem and plays a major role in the development of his own behavior. The main character is always entangled with his complicated behavior which makes him weak with his friends and environment, in the end the main character can develop even better. The purpose of this study is to provide information about the behavior of the main character which has been analyzed from the point of view of psychology and sociology. Keywords: Analyze Behavior, Psychology, Sociology